Whistleblowing in Hungary - Kun, Attila (Towards a Better Protection of Workplace Whistleblowers in the Visegrad Countries, France and Slovenia, 2021)
The aim of this chapter is to take a general account of the past and current practices, experiences and challenges of whistleblowing legislation and whistleblower protection in Hungary. The emphasis will be put on the critical analysis of the currently effective regulatory environment of whistleblowing and whistleblower protection in Hungary, with specific regard to labour law aspects. Furthermore, the context, prospects and basic requirements of the future implementation of the EU Directive will also be highlighted. In this vein, Section 2 sketches the historical, societal and constitutional context. Section 3, as the central part of this study, examines in detail the currently effective legislative framework of whistleblowing in Hungary. Section 4 deals specifically with the labour law-related aspects of whistleblowing, while Section 5 takes a brief look into other related fields of law (including anti-discrimination, criminal law, and trade secrets). Section 6 considers recent and relevant critical opinions and motions for reform. Section 7 looks into the possible challenges and the main tentative tasks of the upcoming transposition of the Directive into Hungarian law. Finally, Section 8 draws some broad, general conclusions.